The implications of increasing temperature due to climate change for asphalt concrete performance and pavement design - Kumlai S. (2017)
© 2017, Korean Society of Civil Engineers and Springer-Verlag Berlin Heidelberg. The dynamic moduli have been recently introduced and effectively used to express the intrinsic behaviour of the viscoelasticity of an asphalt concrete material across a given range of temperatures and frequencies. Those can generally be represented in a form of the master curve. This study investigated the dynamic moduli of Western Australian (WA) asphalt mixes. In addition, the study modified the dynamic modulus predictive equation of the national cooperative highway research program (NCHRP) project 1-37A to suit WA conditions. Furthermore, in this study, the effect of increased temperatures due to climate change upon flexible road pavement was investigated through the pavement design exercise using WA as the study area. To determine the effective dynamic modulus (|E*| eff ), temperature and historical climate data were sourced from a Perth Airport Station to conduct a pavement design exercise. This data covered a 20-year period, a typical asphalt pavement design life. The allowable number of cycles (of traffic) to failure (N f ) under four different pavement design scenarios was then calculated based on this |E*| eff to examine of an increase in temperature potentially resulting from climate change effects. The results of the examination showed that once an increase in temperature due to climate change was taken into account, N f could be decreased by approximately six million repetitions. This equals a shorter pavement life or design period of around four years compared to a result of the original design, which does not consider the increase in temperature resulting from climate change.